Copper Bromide Laser Monitor for Combustion Processes Visualization - Gubarev F. A. Fedor Aleksandrovich; Mostovshchikov A. V. Andrey Vladimirovich; Klenovskii (Klenovsky) M. S. Miron Stanislavovich; Ilyin A. P. Aleksandr Petrovich; Li Lin (2016, 2016)
Title screen